Integration of legislation on countering tax crimes in the EU: opportunities and limitations - D. G. Bachurin (Правоприменение, 2024)
The subject. The article examines the norms of the current tax and criminal legislation of the EU, the experience of which in the future may be in demand in the process of integrating the legal regulation systems of the EAEU states when developing issues of countering tax crimes. The subject of the article is to analyze the problems of: methodology of tax crime research in the EU and data sampling criteria; integration of national tax systems; definition of tax crime in the EU; spread of VAT fraud.Modern law enforcement practice is analyzed using the system-logical method, which indicates the complication of forms of tax evasion and concealment of actual financial and economic transactions.The main results. It is noted that the need for effective law enforcement to ensure the financial stability of states, to counteract distortions of competition resulting from tax evasion is due to the organized and highly structured nature of a significant part of tax crimes, the expansion of the scale of cross-border tax crimes involving foreign elements. The European legislation does not contain a definition of a tax offense as such, but contains a list of types of behavior with specific descriptions of prohibited behavior. It seems that national legislators deliberately preserve a certain amount of ambiguity between prohibited and permitted tax evasion, offering a broad definition of tax evasion, since narrow specifics in the definition of such offenses can lead to undesirable impunity, exclude a flexible approach in responding to changes in this area of legal relations.As a result of the application of the formal legal approach and comparative analysis, conclusions were obtained that, subject to careful preliminary research and practical verification, successful decisions in the field of combating tax evasion and tax fraud adopted in some jurisdictions can be used to improve the legislative provisions of other states.